Checklist of decapods (Crustacea) from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: I. Infraorder Caridea: families Hippolytidae, Lysmatidae, Ogyrididae, Processidae and Thoridae - Terossi, Mariana; Almeida, Alexandre O.; Buranelli, Raquel C.; Castilho, Antonio L.; Costa, Rogério C.; Zara, Fernando J.; Mantelatto, Fernando L. (Zootaxa, 2018)
The current checklist is the result of a long-term multidisciplinary project which combined molecular techniques (mitochondrial DNA markers) and morphological analyses of adult specimens for an accurate and detailed identification of the total biodiversity of decapod crustaceans from marine and coastal (including estuaries) environments of São Paulo State (Brazil). This is the first of a series of reports and providing a checklist of caridean shrimps of the families Hippolytidae (5 spp.), Lysmatidae (6 spp.), Ogyrididae (2 spp.), Processidae (5 spp.) and Thoridae (1 sp.). We collected material of 13 species out of 19 recorded, with sequences of cytochrome oxidase subunit I - barcode region and 16S generated from 10 species. The previous record of Lysmata cf. intermedia for São Paulo is actually L. jundalini, as the first record in São Paulo/South Atlantic waters. The molecular data were helpful to confirm the identification of some species, as the occurrence of L. wurdemanni which is confirmed in the South Atlantic Ocean based on morphological, color pattern and molecular data.